The Role of Colony Temperature in the Entrainment of Circadian Rhythms of Honey Bee Foragers. (26th May 2021) - Giannoni-Guzmán, Manuel A; Rivera-Rodriguez, Emmanuel J; Aleman-Rios, Janpierre; Melendez Moreno, Alexander M; Pérez Ramos, Melina; Pérez-Claudio, Eddie; Loubriel, Darimar; Moore, Darrell; Giray, Tugrul; Agosto-Rivera, Jose L
Abstract: Honey bees utilize their circadian rhythms to accurately predict the time of day. This ability allows foragers to remember the specific timing of food availability and its location for several days. Previous studies have provided strong evidence toward light/dark cycles being the primary Zeitgeber for honey bees. Work in our laboratory described large individual variation in the endogenous period length of honey bee foragers from the same colony and differences in the endogenous rhythms under different constant temperatures. In this study, we further this work by examining the temperature inside the honey bee colony. By placing temperature and light data loggers at different locations inside the colony we measured temperature at various locations within the colony. We observed significant oscillations of the temperature inside the hive, that show seasonal patterns. We then simulated the observed temperature oscillations in the laboratory and found that using the temperature cycle as a Zeitgeber, foragers present large individual differences in the phase of locomotor rhythms for temperature. Moreover, foragers successfully synchronize their locomotor rhythms to these simulated temperature cycles. Advancing the cycle by six hours, resulting in changes in the phase of activity in some foragers in the assay. The results are shown in this study highlight the importance of temperature as a potential Zeitgeber in the field. Future studies will examine the possible functional and evolutionary role of the observed phase differences of circadian rhythms.